Vertical variability of aerosol single-scattering albedo and equivalent black carbon concentration based on in-situ and remote sensing techniques during the iAREA campaigns in Ny-Ålesund. - Markowicz, K. M.; Ritter, Christoph; Lisok, Justyna; Makuch, P.; Stachlewska, I. S.; Cappelletti, D.; Mazzola, M.; Chilinski, M.T. (Atmospheric Environment, 2017)
This work presents a methodology for obtaining vertical profiles of aerosol single scattering properties based on a combination of different measurement techniques. The presented data were obtained under the iAREA (Impact of absorbing aerosols on radiative forcing in the European Arctic) campaigns conducted in Ny-Ålesund (Spitsbergen) during the spring seasons of 2015-2017. The retrieval uses in-situ observations of black carbon concentration and absorption coefficient measured by a micro-aethalometer AE-51 mounted onboard a tethered balloon, as well as remote sensing data obtained from sun photometer and lidar measurements. From a combination of the balloon-borne in-situ and the lidar data, we derived profiles of single scattering albedo (SSA) as well as absorption, extinction, and aerosol number concentration. Results have been obtained in an altitude range from about 400 m up to 1600 m a.s.l. and for cases with increased aerosol load during the Arctic haze seasons of 2015 and 2016. The main results consist of the observation of increasing values of equivalent black carbon (EBC) and absorption coefficient with altitude, and the opposite trend for aerosol concentration for particles larger than 0.3μm. SSA was retrieved with the use of lidar Raman and Klett algorithms for both 532 and 880 nm wavelengths. In most profiles, SSA shows relatively high temporal and altitude variability. Vertical variability of SSA computed from both methods is consistent; however, some discrepancy is related to Raman retrieval uncertainty and absorption coefficient estimation from AE-51. Typically, very low EBC concentration in Ny-Ålesund leads to large error in the absorbing coefficient. However, SSA uncertainty for both Raman and Klett algorithms see ms to be reasonable, e.g. SSA of 0.98 and 0.95 relate to an error of ±0.01 and ±0.025, respectively.